Factors Influencing Occupational Health And Safety (Ohs) Implementation In The Agriculture Sector Of Pakistan: The Moderating Role Of Mimetic Motives - Nadeem, Muhammad Aamir (2025)
Pakistan, being a predominantly agrarian country, has 27 million agrarian workforces. It accounts 37.42 percent of the total workforce but suffering from a highest occupational injuries and diseases rate (i.E., 39 per cent annually). Despite these alarming statistics, not much attention has been given to occupational health and safety (ohs) implementation in this sector. Therefore, this study is aimed at excavating the key factors that can encourage ohs implementation. The proposed model of the study was based on institutional theory. In this regard, the researcher investigated the effect of several factors such as management commitment, safety training, safety communication and feedback, and implementation styles on ohs implementation. This study also examined the moderating role of mimetic motives between these factors and ohs implementation. The data was collected from 311 pakistani agriculture organizations using drop-off pick-up method. The data collection lasted over four and half months starting from august 2021. For statistical analysis, both statistical package for social science (spss) and smartpls were used to analyse the data.